27‐hydroxycholesterol promotes oligodendrocytic maturation: Implications for Alzheimer's disease. (1st February 2022) - Alanko, Vilma; Loera‐Valencia, Raúl; Solomon, Alina; Björkhem, Ingemar; Minguez, Angel Cedazo; Maioli, Silvia; Tabacaru, Graziella; Leal, Maria Latorre; Spanos, Fokion; Quintela‐López, Tania; Gaminde‐Blasco, Adhara; Matute, Carlos; et al.
Abstract: Background: Midlife hypercholesterolemia is an established risk factor for developing Alzheimer's disease (AD), still peripheral cholesterol does not pass the blood‐brain‐barrier (BBB). A proposed factor linking elevated systemic cholesterol levels and AD is the oxidized cholesterol metabolite 27‐hydroxycholesterol (27‐OH) that can pass the BBB. Abnormal myelin structure, resulting in the disconnection of neural networks, is an early phenomenon in AD. It is known that high levels of 27‐OH has a negative impact on the brain, yet its effect on oligodendrocytes remains unexplored. The aim of this project was to determine whether 27‐OH affects brain myelination. Method: Effects of 27‐OH treatment was investigated both in a human cell line and primary cell cultures from mice using mono‐ and co‐culture settings. Behavioural testing of transgenic mice with increased systemic 27‐OH levels (CYP27A1TG) compared to wild type mice was performed and oligodendrocytic markers were examined by immunohistochemical staining and Western blot. Finally, cerebrospinal fluid (CSF) samples from subjective controls (SCI), mild cognitive impairment (MCI) and AD memory clinic patients were analysed for associations between MMSE and RAVLT scores, AD biomarkers, 27‐OH, cholesterol, and myelin proteins. Result: High concentrations of 27‐OH induce cell death in monocultured human oligodendroglioma cells and primary oligodendrocytes. In 3D co‐cultures from embryonic hippocampus and cortex, 27‐OH treatment stimulated oligodendrocyte maturation and not proliferation. CYP27A1TG exhibit cognitive impairment and levels of Myelin Basic Protein (MBP) were increased in brain sections from TG mice compared to wild type, still overall myelin structure was unaltered. Patient CSF levels of the myelination regulating enzyme CNPase was associated to levels of 27‐OH and AD biomarkers. CSF levels of CNPase were increased in MCI compared to SCI but not to AD. Conclusion: The cholesterol metabolism associated 27‐OH alters the rate of differentiation from oligodendrocyte progenitor cells into mature oligodendrocytes without increasing proliferation rate, suggesting that 27‐OH may consequently reduce oligodendrocytic ability for appropriate remodelling in the aging brain. Maintaining or restoring a functional population of oligodendrocyte progenitor cells could possibly diminish the changes in white matter integrity seen in AD, and furthermore support axonal survival.